Identification of cytisine derivatives as agonists of the human delta opioid receptor by supercomputer-based virtual drug screening and transcriptomics - Damiescu, Roxana; Dawood, Mona; Elbadawi, Mohamed; Klauck, Sabine; Bringmann, Gerhard; Efferth, Thomas (ACS chemical biology, 2024)
Delta opioid receptors (DORs) are rising as therapeutic targets, not only for the treatment of pain but also other neurological disorders (e.g., Parkinson’s disease). The advantage of DOR agonists compared to μ-opioid receptor agonists is that they have fewer side effects and a lower potential to induce tolerance. However, although multiple candidates have been tested in the past few decades, none have been approved for clinical use. The current study focused on searching for new DOR agonists by screening a chemical library containing 40,000 natural and natural-derived products. The functional activity of the top molecules was evaluated in vitro through the cyclic adenosine monophosphate accumulation assay. Compound 3 showed promising results, and its activity was further investigated through transcriptomic methods. Compound 3 inhibited the expression of TNF-α, prevented NF-κB translocation to the nucleus, and activated the G-protein-mediated ERK1/2 pathway. Additionally, compound 3 is structurally different from known DOR agonists, making it a valuable candidate for further investigation for its anti-inflammatory and analgesic potential.